Use of phase III slope of volumetric capnography in outpatient clinical practice: a descriptive analysis - Parazzi P.L.F. (2017)
© 2017 Bentham Science Publishers.Background: Volumetric capnography (VCap) is an alternative tool in the search for connections between structural damage and early pulmonary functional changes in chronic respiratory diseases. Thus, numerous markers obtained in VCap, including the inclination curve of phase III (Slp3), have been studied to detect early changes in the airways. Objective: To present the use of Slp3 in different outpatient clinic situations, seeking its better understanding. Method: We performed searches in electronic databases (LILACS, MEDLINE-PubMed, PEDro, and SciELO) for the descriptor “volumetric capnography”. We considered the presence of the descriptors in the title or abstract as a criterion for initial inclusion. All publications until June 2017 were included. Results: In total, 130 studies that addressed the use of Slp3 in clinical practice were identified (109 in PubMed, 10 in LILACS, 10 in SciELO, and one in PEDro). 21 were excluded because of duplicity between databases, and 100 because of the absence of the descriptor in the title and/or abstract or for considering only Slp3 in the invasive mechanical ventilation. Conclusion: In the literature, there is evidence that the evaluation of non-homogeneity of ventilation by Slp3 can identify early lung changes, more specifically of peripheral airways, in individuals with lung disease.